Substitusi Pati Sagu dalam Pembuatan Mi Basah dengan Penambahan Sari Wortel (Daucus carrota L) - Batuwael, Tusye F; Polnaya, Febby J; Augustyn, Gelora H (Pattimura University Ambon Maluku Indonesia, 2023)
Wet noodles with carrot extract (Daucus carrota L.) are one of the diversified products from carrots to increase the added value. This study aimed to determine the best carrot extract treatment for making wet noodles. This study was designed using a completely randomized design with a single factor, namely the substitution of sago starch in the manufacture of wet noodles with the addition of carrot extract repeated twice. The results showed that based on the physicochemical results, the addition of 500 g carrots was the best treatment with a moisture content of 49.36%, an ash content of 1.26%, a protein content of 7.97%, a fat content of 1.21%, a carbohydrate content of 40.20%, a water absorption of 0.54%, and a cooking loss of 9.83%.